Exchange and cooperation between Korea and Kazakhstan to overcome Covid-19 (Focusing on Newspaper articles from 『Hаnin Shinmun』 and 『Kore Ilbo』 in 2020-21 years) (Journal of Oriental Studies, 2023)
During the past 2020-21, COVID-19 has had a profound impact on our lives to the extent of changing the paradigm of life. In this paper, I paid attention to the exchange and cooperation between Kazakhstan and Korea to overcome COVID-19 in 2020-21. In other words, I looked at how COVID-19 affected exchanges and cooperation between Kazakhstan and Korea during that period. In other words, what types of exchanges and cooperation took place, and whether exchanges and cooperation decreased or increased compared to the previous period. To see specific examples of exchange and cooperation between Kazakhstan and Korea to overcome COVID-19, I used articles from 『Hanin Shinmun』 (The Korean Newspaper), the representative weekly magazine of the korean community from Republic of Korea in Kazakhstan, and 『Kore Ilbo』, the representative weekly magazine of the Koryein community(ethnic korean from Kazakhstan). In the article search process, I preferentially included articles that directly show the mutual exchange and cooperation between Kazakhstan and Korea related to COVID-19. In addition, although not related to COVID-19, I also included articles showing general mutual exchanges and cooperation showing the relationship between Kazakhstan and Korea at that time in the scope of the study. This study is meaningful not only in terms of exchange and cooperation to overcome COVID-19, but also in that it can help identify the actual mutual relationship between the two countries.